Extracellular bacterial synthesis of protein-functionalized ferromagnetic Co3O4 nanocrystals and imaging of self-organization of bacterial cells under stress after exposure to metal ions - Kumar, Umesh; Shete, Ashvini; Harle, Arti S.; Kasyutich, Oksana; Schwarzacher, W.; Pundle, Archana; Poddar, Pankaj (Chemistry of Materials, 2008)
Co3O4, which crystallizes in the spinet phase at temperatures much higher than ambient temperatures, orders antiferromagnetically below its Neel temperature (similar to 40 K). However, in nanosize, it shows ferromagnetic ordering due to surface canting, disorder, imperfect oxygen atom coordination, etc. Here, for the first time, we report the synthesis of single-crystalline, ferromagnetic Co3O4 nanoparticles functionalized with proteins (size 5-7 nm) using cobalt acetate as precursor at room temperature in aqueous medium by a metal-tolerant marine bacterium isolated from the coast of the Arabian Sea. Energetically unfavorable change in the oxidation state of Co atoms from (+2 to +3) during synthesis by the bacterial strain was evidenced by X-ray photoelectron spectroscopy. The effect on the morphology of bacterial cells after exposure to the cobalt acetate was imaged by scanning electron microscopy showing cooperative, self-organized. structured colony formation, possibly due to the interbacterial communication under external stress.

Kinetics of PbCrO(4) nanorod growth by oriented attachment at the air-water interface - Hawaldar, Ranjit R.; Sathaye, Shivaram D.; Harle, Arti S.; Gholap, Ramkrishna S.; Patil, Kashinath R. (Journal of Physical Chemistry C, 2008)
Oriented attachment is a new way of crystal growth to transform preformed nanoparticles into hierarchical assemblies. Here, we demonstrate the use of liquid-liquid interfaces toward the formation of PbCrO(4) nanoparticles and their subsequent time-dependent self-assembly at the air-water interface into nanorods by oriented attachment. EDAX and XPS analysis indicate the formation of stoichiometric PbCrO(4). TEM studies at different stages of aging reveal that the transformation from nanoparticles to nanorods is kinetically governed. HRTEM analysis indicates nanorod growth along the [110] plane. UV-visible spectra reveal the presence of peaks at 425 and 515 nm for nanorods, while for the nanoparticle sample, a single peak at 425 urn is evident. As formation of ultrathin films over a large area (typically equal to or greater than 1 mu m x 1 mu m) concomitantly accompanies this approach, it can be extended to other materials as well for nanostructured device applications.

Sulfur nanoparticles synthesis and characterization from H2S gas, using novel biodegradable iron chelates in w/o microemulsion - Deshpande, Aniruddha S.; Khomane, Ramdas B.; Vaidya, Bhalchandra K.; Joshi, Renuka M.; Harle, Arti S.; Kulkarni, Bhaskar D. (Nanoscale Research Letters, 2008)
Sulfur nanoparticles were synthesized from hazardous H2S gas using novel biodegradable iron chelates in w/o microemulsion system. Fe3+-malic acid chelate (0.05 M aqueous solution) was studied in w/o microemulsion containing cyclohexane, Triton X-100 and n-hexanol as oil phase, surfactant, co-surfactant, respectively, for catalytic oxidation of H2S gas at ambient conditions of temperature, pressure, and neutral pH. The structural features of sulfur nanoparticles have been characterized by X-ray diffraction (XRD), transmission electron microscope (TEM), energy dispersive spectroscopy (EDS), diffused reflectance infra-red Fourier transform technique, and BET surface area measurements. XRD analysis indicates the presence of alpha-sulfur. TEM analysis shows that the morphology of sulfur nanoparticles synthesized in w/o microemulsion system is nearly uniform in size (average particle size 10 nm) and narrow particle size distribution (in range of 5-15 nm) as compared to that in aqueous surfactant systems. The EDS analysis indicated high purity of sulfur (> 99%). Moreover, sulfur nanoparticles synthesized in w/o microemulsion system exhibit higher antimicrobial activity (against bacteria, yeast, and fungi) than that of colloidal sulfur.
Keywords: Antimicrobial activity; H2S gas; iron chelates; sulfur nanoparticles; w/o microemulsion

Development of a novel method to grow mono-/few-layered MoS2 films and MoS2-graphene hybrid films for supercapacitor applications - Patil, Sagar; Harle, Arti S.; Sathaye, Shivaram; Patil, Kashinath (CrystEngComm, 2014)
The controlled synthesis of highly crystalline MoS2 atomic layers remains a challenge for practical applications of this emerging material. We demonstrate a facile method to synthesize crystalline mono-layered/few-layered MoS2 thin films at the liquid-liquid interface which can be suitably transferred to the substrates. The films are characterized by XRD for their crystal structure and by SEM and TEM for the morphology. MoS2 nanosheet-graphene nanosheet (MoS2-GNS) hybrid films have been developed by the application of layer-by-layer (LbL) techniques. Cyclic voltammetry and other electrochemical characterization techniques reveal that the hybrid film electrode shows a specific capacitance of 282 F g(-1) at a scan rate of 20 mV s(-1). The as-obtained hybrid electrode is robust and exhibits much improved cycle life (>1000), retaining over 93% of its initial capacitance as revealed by galvanostatic charge/discharge studies. The confirmation of better performance as a supercapacitor of the composite was studied by electrochemical impedance spectroscopy. These results indicate that the MoS2-GNS hybrid is a promising candidate for the electrode material in supercapacitor applications.